Biochemical and functional properties of sardinella (Sardinella aurita) by-product hydrolysates - Souissi, Nabil (Array, 2007)
Fish protein hydrolysates (FPHs) with different degrees of hydrolysis (DH of 6.62, 9.31 and 10.16) were prepared from heads and viscera of sardinella (Sardinella aurita) by treatment with Alcalase®. The liquid hydrolysates were spray dried. All spray dried by-product hydrolysates contained 73 to 75 % of proteins and low content of lipids. Reversed-phase HPLC profiles showed that low DH hydrolysates contained high hydrophobic peptides and the extent of hydrolysis resulted in an increase of fish hydrophilic peptides. Some functional properties of FPHs were assessed and compared with those of casein or the undigested sardinella protein. Solubility increased while emulsifying capacity and whippability decreased with the increase in the degree of hydrolysis. The product, with a DH of 10.16 %, had an excellent solubility (100 %) over a pH range of 6.0–10.0. The antioxidant activity of the hydrolysates was also tested. All FPHs exhibited more than 50 % inhibition of linoleic acid peroxidation. The antioxidant activity of FPH with 10.16 % DH was about 73 % of that of a-tocopherol, a natural antioxidative agent